Determination of the Tanjung Karang Religious Court on the Origin of Children Outside of Marriage from the Perspective of Islamic Family Law (Study of Decision Number 115/Pdt. P/2024/P. Tnk) - Sukron Amin; Mohammad Yasir Fauzi; Akhmad Ikhwani (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2026)
This study examines the legal status of children born from unregistered (sirri) marriages, namely marriages conducted according to religious law but not officially registered with the Office of Religious Affairs (KUA). The absence of official registration frequently results in such children being categorized as children born outside lawful marriage, thereby creating legal problems related to their status, identity, and civil rights. This research discusses the legal position of children born from unregistered marriages, forms of legal protection through judicial determination of lineage, and judges' considerations in deciding such cases based on Islamic Family Law. The study aims to analyze the legal status of children, examine legal protections available through the determination of lineage, and explain the legal reasoning applied by religious court judges. This research employs a normative juridical method using a library research approach. Primary data were obtained from the Decision of the Tanjung Karang Religious Court Number 115/Pdt.P/2024/PA. Tnk, Law Number 1 of 1974 concerning Marriage, Constitutional Court Decision Number 46/PUU-VIII/2010, and the Compilation of Islamic Law. Secondary data were collected from books, academic journals, and relevant previous studies. The findings indicate that the legal status of children may be strengthened through judicial determination of lineage in religious courts, which serves as the basis for recognizing civil relations with biological parents and issuing birth certificates. Nevertheless, the court ruling still classified the child as born outside a legally recognized marriage. From the perspective of Islamic law, the child's civil rights remain primarily limited to the mother and the maternal family.